2020
DOI: 10.1029/2020ja028198
|View full text |Cite
|
Sign up to set email alerts
|

New Insights From Long‐Term Measurements of Inner Belt Protons (10s of MeV) by SAMPEX, POES, Van Allen Probes, and Simulation Results

Abstract: The Solar, Anomalous, and Magnetospheric Particle Explorer (SAMPEX) mission provided long‐term measurements of 10s of megaelectron volt (MeV) inner belt (L < 2) protons (1992–2009) as did the Polar‐orbiting Operational Environmental Satellite‐18 (POES‐18, 2005 to present). These long‐term measurements at low‐Earth orbit (LEO) showed clear solar cycle variations which anticorrelate with sunspot number. However, the magnitude of the variation is much greater than the solar cycle variation of galactic cosmic rays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 52 publications
2
31
1
Order By: Relevance
“…Moreover, the radiation flux at higher L ‐values ( L > 1.7) is controlled both by the atmospheric density (loss process) and the GCR flux variations (source process). They are feasible because the drift particles at L < 2 (whole Hisaki orbit), as they fly at very low altitudes at the SAA, are strongly affected by atmospheric density variations, and the sensitivity to the GCR flux is higher at higher L ‐values (Li et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the radiation flux at higher L ‐values ( L > 1.7) is controlled both by the atmospheric density (loss process) and the GCR flux variations (source process). They are feasible because the drift particles at L < 2 (whole Hisaki orbit), as they fly at very low altitudes at the SAA, are strongly affected by atmospheric density variations, and the sensitivity to the GCR flux is higher at higher L ‐values (Li et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty in the electron fluxes caused by the uncertainties in the input parameters is outside the scope of the current study and will be quantitatively analyzed in a future study (e.g., the comprehensive analysis in Licata et al, 2020). (Baker et al, 1993;Cook et al, 1993;Li et al, 2020;Selesnick, 2015). Since SAMPEX is located at LEO orbit, it measures electrons with a very small range of equatorial pitch angles very close to the loss cone, in contrast to the Van Allen Probes which observed the full equatorial pitch angle distribution, and thus the two datasets are closely correlated but not identical to each other, so the comparison is only qualitative (Kanekal et al, 2001;Li et al, 2013Li et al, , 2017Zhang, Li, et al, 2020).…”
Section: Model Performancementioning
confidence: 99%
“…We emphasize that the errors are contributed from both the error of the ORIENT-R model and the error in the predicted AL index. Nevertheless, the good correlation coefficient shows the out-of-sample predictive capability of the ORI-ENT-R model on the Van Allen Probes data set.The trapped electron fluxes reconstructed by the ORIENT-R model can be further validated in a completely out-of-sample fashion using the ∼2 MeV electron fluxes measured by the Proton-Electron Telescope on the Solar Anomalous and Magnetospheric Particle Explorer (SAMPEX) satellite, which is located in a polar-orbiting LEO (launched into a 690 × 510 km altitude and 82° inclination orbit in July of 1992, and decayed to ∼490 × 410 km by 2009)(Baker et al, 1993;Cook et al, 1993;Li et al, 2020;Selesnick, 2015). Since SAMPEX is located at LEO orbit, it measures electrons with a very small range of equatorial pitch angles very close to the loss cone, in contrast to the Van Allen Probes which observed the full equatorial pitch angle distribution, and thus the two datasets are closely correlated but not identical to each other, so the comparison is only qualitative(Kanekal et al, 2001;Li et al, 2013Li et al, , 2017Zhang, Li, et al, 2020).…”
mentioning
confidence: 99%
“…Our current knowledge of the solar-cycle variations of the low-altitude proton environment essentially relies on the long-term measurements below 250 MeV made by a few LEO missions, including the NOAA Polar Orbiting Environmental Satellite (since 1978) series at an ∼800-850 km altitude (e.g., Huston et al (1996Huston et al ( , 1998; Qin et al (2014)), and the Solar, Anomalous, andMagnetospheric Particle Explorer (1992-2012), launched into a ∼510-690 km altitude orbit (e.g., Li et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…The proton flux was found to rapidly decrease in the solar-maximum phases and slowly increase approaching solar minima. In particular, it was shown that the intensity variations are anticorrelated with those of the solar radio flux at 10.7 cm (also called the F 10.7 index), commonly used as a proxy of the corona activity and as an input to atmospheric models, with an energy-and L-dependent phase lag (Huston et al 1996(Huston et al , 1998Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%